Answer:
- f = -2/5a +14
- 12.4 ≈ 12 fish for 4 algae blooms
Step-by-step explanation:
The 2-point form of the equation for a line is useful when you are given two points to work with:
y = (y2 -y1)/(x2 -x1)(x -x1) +y1
The independent variable (x) is apparently "algae blooms" and is to be represented by "a". The dependent variable (y) is "number of fish" and is to be represented by "f". So, we have ...
f = (4 -10)/(25 -10)(a -10) +10
f = -6/15(a -10) +10
f = -2/5a +14 . . . an equation for the scenario
Four a=4, the fish population is predicted to be ...
f = -2/5(4) +14 = 12.4
There will be about 12 fish when there are 4 algae blooms.
Since
are in arithmetic progression,
![a_2 = a_1 + 2](https://tex.z-dn.net/?f=a_2%20%3D%20a_1%20%2B%202)
![a_3 = a_2 + 2 = a_1 + 2\cdot2](https://tex.z-dn.net/?f=a_3%20%3D%20a_2%20%2B%202%20%3D%20a_1%20%2B%202%5Ccdot2)
![a_4 = a_3+2 = a_1+3\cdot2](https://tex.z-dn.net/?f=a_4%20%3D%20a_3%2B2%20%3D%20a_1%2B3%5Ccdot2)
![\cdots \implies a_n = a_1 + 2(n-1)](https://tex.z-dn.net/?f=%5Ccdots%20%5Cimplies%20a_n%20%3D%20a_1%20%2B%202%28n-1%29)
and since
are in geometric progression,
![b_2 = 2b_1](https://tex.z-dn.net/?f=b_2%20%3D%202b_1)
![b_3=2b_2 = 2^2 b_1](https://tex.z-dn.net/?f=b_3%3D2b_2%20%3D%202%5E2%20b_1)
![b_4=2b_3=2^3b_1](https://tex.z-dn.net/?f=b_4%3D2b_3%3D2%5E3b_1)
![\cdots\implies b_n=2^{n-1}b_1](https://tex.z-dn.net/?f=%5Ccdots%5Cimplies%20b_n%3D2%5E%7Bn-1%7Db_1)
Recall that
![\displaystyle \sum_{k=1}^n 1 = \underbrace{1+1+1+\cdots+1}_{n\,\rm times} = n](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bk%3D1%7D%5En%201%20%3D%20%5Cunderbrace%7B1%2B1%2B1%2B%5Ccdots%2B1%7D_%7Bn%5C%2C%5Crm%20times%7D%20%3D%20n)
![\displaystyle \sum_{k=1}^n k = 1 + 2 + 3 + \cdots + n = \frac{n(n+1)}2](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bk%3D1%7D%5En%20k%20%3D%201%20%2B%202%20%2B%203%20%2B%20%5Ccdots%20%2B%20n%20%3D%20%5Cfrac%7Bn%28n%2B1%29%7D2)
It follows that
![a_1 + a_2 + \cdots + a_n = \displaystyle \sum_{k=1}^n (a_1 + 2(k-1)) \\\\ ~~~~~~~~ = a_1 \sum_{k=1}^n 1 + 2 \sum_{k=1}^n (k-1) \\\\ ~~~~~~~~ = a_1 n + n(n-1)](https://tex.z-dn.net/?f=a_1%20%2B%20a_2%20%2B%20%5Ccdots%20%2B%20a_n%20%3D%20%5Cdisplaystyle%20%5Csum_%7Bk%3D1%7D%5En%20%28a_1%20%2B%202%28k-1%29%29%20%5C%5C%5C%5C%20~~~~~~~~%20%3D%20a_1%20%5Csum_%7Bk%3D1%7D%5En%201%20%2B%202%20%5Csum_%7Bk%3D1%7D%5En%20%28k-1%29%20%5C%5C%5C%5C%20~~~~~~~~%20%3D%20a_1%20n%20%2B%20%20n%28n-1%29)
so the left side is
![2(a_1+a_2+\cdots+a_n) = 2c n + 2n(n-1) = 2n^2 + 2(c-1)n](https://tex.z-dn.net/?f=2%28a_1%2Ba_2%2B%5Ccdots%2Ba_n%29%20%3D%202c%20n%20%2B%202n%28n-1%29%20%3D%202n%5E2%20%2B%202%28c-1%29n)
Also recall that
![\displaystyle \sum_{k=1}^n ar^{k-1} = \frac{a(1-r^n)}{1-r}](https://tex.z-dn.net/?f=%5Cdisplaystyle%20%5Csum_%7Bk%3D1%7D%5En%20ar%5E%7Bk-1%7D%20%3D%20%5Cfrac%7Ba%281-r%5En%29%7D%7B1-r%7D)
so that the right side is
![b_1 + b_2 + \cdots + b_n = \displaystyle \sum_{k=1}^n 2^{k-1}b_1 = c(2^n-1)](https://tex.z-dn.net/?f=b_1%20%2B%20b_2%20%2B%20%5Ccdots%20%2B%20b_n%20%3D%20%5Cdisplaystyle%20%5Csum_%7Bk%3D1%7D%5En%202%5E%7Bk-1%7Db_1%20%3D%20c%282%5En-1%29)
Solve for
.
![2n^2 + 2(c-1)n = c(2^n-1) \implies c = \dfrac{2n^2 - 2n}{2^n - 2n - 1} = \dfrac{2n(n-1)}{2^n - 2n - 1}](https://tex.z-dn.net/?f=2n%5E2%20%2B%202%28c-1%29n%20%3D%20c%282%5En-1%29%20%5Cimplies%20c%20%3D%20%5Cdfrac%7B2n%5E2%20-%202n%7D%7B2%5En%20-%202n%20-%201%7D%20%3D%20%5Cdfrac%7B2n%28n-1%29%7D%7B2%5En%20-%202n%20-%201%7D)
Now, the numerator increases more slowly than the denominator, since
![\dfrac{d}{dn}(2n(n-1)) = 4n - 2](https://tex.z-dn.net/?f=%5Cdfrac%7Bd%7D%7Bdn%7D%282n%28n-1%29%29%20%3D%204n%20-%202)
![\dfrac{d}{dn} (2^n-2n-1) = \ln(2)\cdot2^n - 2](https://tex.z-dn.net/?f=%5Cdfrac%7Bd%7D%7Bdn%7D%20%282%5En-2n-1%29%20%3D%20%5Cln%282%29%5Ccdot2%5En%20-%202)
and for
,
![2^n > \dfrac4{\ln(2)} n \implies \ln(2)\cdot2^n - 2 > 4n - 2](https://tex.z-dn.net/?f=2%5En%20%3E%20%5Cdfrac4%7B%5Cln%282%29%7D%20n%20%5Cimplies%20%5Cln%282%29%5Ccdot2%5En%20-%202%20%3E%204n%20-%202)
This means we only need to check if the claim is true for any
.
doesn't work, since that makes
.
If
, then
![c = \dfrac{4}{2^2 - 4 - 1} = \dfrac4{-1} = -4 < 0](https://tex.z-dn.net/?f=c%20%3D%20%5Cdfrac%7B4%7D%7B2%5E2%20-%204%20-%201%7D%20%3D%20%5Cdfrac4%7B-1%7D%20%3D%20-4%20%3C%200)
If
, then
![c = \dfrac{12}{2^3 - 6 - 1} = 12](https://tex.z-dn.net/?f=c%20%3D%20%5Cdfrac%7B12%7D%7B2%5E3%20-%206%20-%201%7D%20%3D%2012)
If
, then
![c = \dfrac{24}{2^4 - 8 - 1} = \dfrac{24}7 \not\in\Bbb N](https://tex.z-dn.net/?f=c%20%3D%20%5Cdfrac%7B24%7D%7B2%5E4%20-%208%20-%201%7D%20%3D%20%5Cdfrac%7B24%7D7%20%5Cnot%5Cin%5CBbb%20N)
There is only one value for which the claim is true,
.
Answer:
D. 2 3 • 3 2 • 5
Step-by-step explanation:
ig I need at least 20 characters to submit my answer. :)
Y = 7sin(30) = 3.5
_________